Prognostic potential of tumor lesions of the lower uterine segment in early endometrioid cancer of the uterine body - B. E. Tkachenko; L. S. Mkrtchian; I. A. Zamulaeva; A. B. Galitsyna; E. V. Sheberova; T. А. Agababyan; S. A. Ivanov; A. D. Kaprin (Исследования и практика в медицине, 2025)
In modern clinical practice, when deciding on the amount of adjuvant therapy for cancer of the uterine body (UBC), such a factor as a tumor lesion of the lower uterine segment (LUS) is not considered, although a number of studies indicate its possible connection with a more aggressive course of the disease.Purpose of the study. To study the relationship between tumor involvement of the LUS and traditional clinical and morphological prognostic factors, and the impact of this parameter on the treatment outcomes of early endometrial cancer.Patients and methods. The study included 506 patients with stage I endometrioid UBC according to the classification of the International Federation of Gynecologists and Obstetricians (FIGO) who underwent surgical or combined treatment at the A. Tsyb Medical Radiological Research Center – Branch of the National Medical Research Radiological Center (Obninsk, Russian Federation) in 2002–2024. The median follow-up was 81.1 months. The patients were divided into two groups depending on the presence or absence of a tumor lesion of the LUS according to the histological conclusion: respectively Group 1–175 (34.6 %) patients, group 2–331 (65.4 %) patients.Results. LUS involvement was found in 34.6 % of patients. It was found that these patients more often had factors such as lymphovascular invasion (LVI) (p < 0.001) and deep invasion into the myometrium (p < 0.001). Overall, LUS involvement was recorded in 23 % of patients without traditional unfavorable prognostic factors and in 50 % of patients with these factors (p < 0.001). At the same time, more common forms of the disease affecting the pathomorphological stage were more frequently detected in the group of patients with LUS involvement – 20.0 % versus 5.1 % in the group without LUS involvement (p < 0.001). Thus, in cases of LUS involvement, the risk of detecting a more common tumor process after histological examination increases 3.9 times compared to cases without LUS involvement. Survival analysis at the current follow-up period showed a statistically significant decrease in overall and five-year survival rates in patients with stage I UBC with LUS involvement – 87.9 % and 75.3 ± 4.8 %, respectively, compared with 93.4 % and 93.1 ± 2.5 % without LUS involvement (with p = 0.044 and p < 0.001, respectively).Conclusion. Tumor involvement of the LUS can be considered a potential diagnostic predictor for the detection of more common forms of stage I UBC and a prognostic indicator of an unfavorable outcome of endometrioid disease.